The influence of lung volume during imaging on CFD within realistic airway models. Issue 2 (1st February 2017) - Katz, Ira; Pichelin, Marine; Montesantos, Spyridon; Murdock, Alexander; Fromont, Samuel; Venegas, Jose; Caillibotte, Georges
ABSTRACT: In this article, we address a fundamental question regarding computational fluid dynamics (CFD) modeling within lung airways: does the inhaled volume during imaging have a significant effect on CFD computations of aerosol deposition? High resolution computed tomography (HRCT) images taken at mean lung volume (MLV) and at total lung capacity (TLC) obtained as part of a previous study of ventilation and aerosol deposition using positron emission tomography (PET) in challenged asthmatics were utilized to construct two airway models for each subject, and the differences in CFD calculated deposition metrics were subsequently quantified. These models included all the airway generations that could be rendered from the HRCT images. CFD calculations for three inhalation flow rates and four monodisperse aerosol sizes used images at MLV and at TLC from 24 volunteer subjects. Both large scale and detailed measures of particle deposition distribution were used in the analysis. The influence of lung volume during imaging is to increase airway dimensions in realistic models and thus reduce flow velocity and deposition due to impaction in the upper airways as calculated by CFD. However, large-scale deposition measures are confounded when the TLC models include deeper generations in the lung that increase the total airway deposition. These trends are modulated by the flow and particle characteristics of the aerosol, making consistent quantifiable differences between MLV and TLC difficult to predict unless both models consider the same anatomical airways. © 2017 American Association for Aerosol Research